Boundary crossing and identity re-negotiation in internships: The integrative, future-oriented and transformational potential of interns' identity project. (March 2020) - Popov, Jelena
Abstract: This paper explores students' and recent graduates' experience of boundary-crossing in an internship. It draws on the dialogical approach to focus group to show how young people's reflections on their internship experience suggest the importance of their identity project. In particular, the paper argues that interns' identity projects can be seen as semiotic resources that are (i) articulated, refined or enhanced through internship experience and (ii) driving future cycles of boundary crossing by shaping their plans for the future. The interns' identity project is, on one hand, consequential or emerges from past activities and integrates preference, values and commitments into a coherent narrative whole. On the other hand, the identity project informs plans, preferences and orientations to future and shapes how young people create their professional and personal trajectories.